CFD study on electrolyte distribution in redox flow batteries. (October 2015) - Bortolin, S; Toninelli, P; Maggiolo, D; Guarnieri, M; Del Col, D
Abstract: The most important component in a redox flow battery (RFB) cell is the MEA (membrane electrode assembly), a sandwich consisting of two catalyzed electrodes with an interposed polymeric membrane. In order to allow electrolyte flow toward the electroactive sites, the electrodes have a porous structure that can be obtained with carbon base materials such as carbon felts. The RFB cell is closed by two plates containing the distribution flow channels. Considering that a uniform electrolyte distribution in the reaction region is a prerequisite for high-efficiency operation, the flow pattern is an important parameter to be investigated for the optimization of the cell. In the present work, the effect of different channels patterns on the electrolyte distribution and on the pressure drop is numerically investigated. Three-dimensional simulations have been carried out with ANSYS Fluent code and four different layouts have been considered. Calculations have been performed both in the distribution channels and in the felt porous region.